Sedation for less invasive surfactant administration in preterm infants: a systematic review and meta-analysis - Moschino, L; Ramaswamy, VV; Reiss, IKM; Baraldi, E; Roehr, C; Simons, SHP (Springer Nature, 2022)
Background: Sedation to preterm neonates receiving Less Invasive Surfactant Administration (LISA) for respiratory distress syndrome (RDS) is controversial.